Effect of the ruminal liquid extraction method in the in vitro gas technique - Ramírez Díaz, Roselia; Pinto Ruiz, René; Guevara Hernández, Francisco; Venegas Venegas, José Apolonio; Reyes Sosa, Mariela Beatriz; Miranda Romero, Luis Alberto; Miranda Romero, Luis Alberto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
In vitro gas studies require the use of cannulated animals; however, the high cost of the surgery limits its application. Therefore, the objective of the study was to evaluate the effect of the ruminal fluid extraction technique by oro-ruminal probe affects the results derived from the in vitro gas production technique (GPT). Elaeis guineensis meal was used as a substrate. Ruminal fluid was obtained in two ways: cannulated animals and oro-ruminal probe. Dry matter degradation was estimated (DMD), parameters of fermentation kinetics and fractional volume by the GPT. The comparison of means was carried out using the Tukey procedure (p<0,05). The results indicated the lack of significant statistical differences (p>0,05). It was concluded that the ruminal fluid extraction technique did not modify the DGRMS, the parameters and fermentation fractions of E. guineensis.